Almond cold-pressed oil by-product as ingredient for cookies with potential health benefits: chemical and sensory evaluation - Barreira, João C.M. (2018)
tNowadays, food security is a global concern and a great scientific challenge. Agro-industrial by-productscan be used as potential ingredients of innovative food products, contributing to solve this societaldemand. By-products of high specialty oils processing, for instance, have remarkable nutritional andorganoleptic properties. Accordingly, the partially delipidified almond flour (PDAF) remaining fromalmond oil extraction, was used as an alternative ingredient in a highly appreciated almond-based cookie(“almendrados”). For comparison purposes, four different “almendrados” formulations (one industrial,two with PDAF, and one with whole almond flour), were compared regarding nutritional composition,vitamin E and fatty acids profiles. To assess the cookie sensory properties, seventy-four consumers eval-uated “appearance”, “taste”, “sweetness”, “crunchiness”, “hardness”, “overall quality” using adequatehedonic scales. Fat and protein levels showed significant differences among industrial and the otherthree samples. Cookies with PDAF presented similar tocopherols and fatty acids to the traditional (moreexpensive) formulation, besides reaching the highest scores on “appearance”, “sweetness”, “hardness”,“overall quality” and “buying predisposition” parameters. Accordingly, the incorporation of PDAF mightrepresent an effective way of adding value to an industrial by-product, while providing a pleasant novelcookie formulation.